Pathological glycogenesis through glycogen synthase 1 and suppression of excessive AMP kinase activity in myeloid leukemia cells - Bhanot, Haymanti; Podar, Klaus (Leukemia, 2015)
The rapid proliferation of myeloid leukemia cells is highly dependent on increased glucose metabolism. Through an unbiased metabolomics analysis of leukemia cells, we found that the glycogenic precursor UDP-D-glucose is pervasively upregulated, despite low glycogen levels. Targeting the rate-limiting glycogen synthase 1 (GYS1) not only decreased glycolytic flux but also increased activation of the glycogen-responsive AMP kinase (AMPK), leading to significant growth suppression. Further, genetic and pharmacological hyper-activation of AMPK was sufficient to induce the changes observed with GYS1 targeting. Cancer genomics data also indicate that elevated levels of the glycogenic enzymes GYS1/2 or GBE1 (glycogen branching enzyme 1) are associated with poor survival in AML. These results suggest a novel mechanism whereby leukemic cells sustain aberrant proliferation by suppressing excess AMPK activity through elevated glycogenic flux and provide a therapeutic entry point for targeting leukemia cell metabolism.